Potential utilization of the absolute point cumulative semivariogram technique for the evaluation of distribution coefficient - Kulahci, Fatih; Sen, Zekai (Elsevier Science Bv, 2009)
The classical solid/liquid distribution coefficient, K(d), for radionuclides in water-sediment systems is dependent on many parameters such as flow, geology, pH, acidity, alkalinity, total hardness, radioactivity concentration, etc. in a region. Considerations of all these effects require a regional analysis with an effective methodology, which has been based on the concept of the cumulative semivariogram concept in this paper. Although classical K(d) calculations are punctual and cannot represent regional pattern, in this paper a regional calculation methodology is suggested through the use of Absolute Point Cumulative SemiVariogram (APCSV) technique. The application of the methodology is presented for (137)Cs and (90)Sr measurements at a set of points in Keban Dam reservoir, Turkey. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Semivariogram; Spatial distribution; Radionuclides; Distribution coefficient; Model